The effect of adding Rosmarinic and Ascorbic acids to vitrification media on fertilization rate of the mice oocyte: An experimental study - Abdollah Borjizadeh; Hamid Ahmadi; Erfan Daneshi; Daem Roshani; Fardin Fathi; Mahdad Abdi; Sherko Nasseri; Morteza Abouzaripour (Shahid Sadoughi University of Medical Sciences, 2019)
Background Oocytes vitrification is a pivotal step for the widespread and safekeeping of animal genetic resources. Oocytes endure notable morphological and functional damage during cryopreservation. Oxidative stress is one of the adverse effects that vitrification imparts on oocytes. Objective In the present study, we investigated the antioxidant effect of Rosmarinic and Ascorbic acids on the quality and fertilizing ability of frozen-thawed mice oocyte. Materials and Methods In this experimental study, germinal vesicle oocytes obtained from two-months-old (30-40gr) NMRI mice were randomly divided into four groups. The basic cryoprotectants were 7.5% (v/v) ethylene glycol+7.5% (v/v) Propanediol as an equilibration media. Vitrification medium contained 15% (v/v) ethylene glycol+15% (v/v) propanediol, and 0.5 M sucrose. In the first group (Control), nothing was added to vitrification mediums, whereas, in the second and third groups, 0.5 mmol/L of Ascorbic acid and 105 µmol/L of Rosmarinic acid were added into vitrification medium, respectively. The cumulative concentration of Rosmarinic and Ascorbic acids were added to group 4. Mouse oocytes were vitrified and preserved for one month. The thawed oocytes were transferred into the α-MEM medium (Alpha Minimum Essential Medium) and maintained in this medium for 24 hr, to be matured and reach the metaphase II stage. Results The addition of Rosmarinic and Ascorbic acids to the vitrification solution improved the survival, maturation of Germinal vesicles, fertilization rate, and finally development to 4-cell stage. Maturation rates to 4-cell stage for Ascorbic acid, Rosmarinic acid, and both of them together were 80%, 80.76%, and 86.61%, respectively. Conclusion These results indicate that the addition of a cumulative concentration of 0.5 mmol/L Ascorbic acid and 105 µmol/L of Rosmarinic acid to the cryopreservation solution for the mouse immature oocytes would be of significant value (p < 0.01).